2004
DOI: 10.1080/15438620490497503
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Activation Pattern of Hip Arthroplasty Patients in Walking

Abstract: The authors gratefully acknowledge the work and assistance of K. Brettmann and C. Allerlei during this research project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
8
1
2
Order By: Relevance
“…By placing their hip in this less adducted position, THA patients required a smaller hip abduction moment to counteract an opposing moment produced by their centre of mass, and to thus stabilise their pelvis in the frontal plane. It has been speculated that this altered gait pattern results from a weakness of the hip abductors [8,9]. Given that muscle strength at the hip was not measured in the present study, we cannot confirm this plausible speculation.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…By placing their hip in this less adducted position, THA patients required a smaller hip abduction moment to counteract an opposing moment produced by their centre of mass, and to thus stabilise their pelvis in the frontal plane. It has been speculated that this altered gait pattern results from a weakness of the hip abductors [8,9]. Given that muscle strength at the hip was not measured in the present study, we cannot confirm this plausible speculation.…”
Section: Discussioncontrasting
confidence: 57%
“…In fact, several researchers have hypothesised that such muscle weakness is responsible for gait adaptations that have been found to be present following THA [8][9][10]. In comparison with healthy individuals, THA patients generally exhibit lower hip adduction and extension angles, and thus generate lower hip abduction and extension moments of force during level walking [8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, recent studies demonstrated that an asynchronous oscillation of the pelvis can be measured 24-42 days [2], 6 weeks and 16 weeks postoperatively [3] using an instrumented gait analysis. Interestingly, the altered synchronicity does not necessarily coincide with decreased range of motion (ROM) in the frontal plane [4]. In a subjective appraisal of gait pattern Sander et al detected Trendelenburg gait in the same amount of patients in a pre-test and 5 weeks after THR.…”
Section: Introductionmentioning
confidence: 99%
“…18 A csípőízületi endoprotézis beültetés a fájdal-mat megszünteti, a funkcionális képességeket részben visszaállítja, [19][20][21] de a posztoperatív időszak alatt a járásminta lényegesen módo-sul. 4,[22][23][24][25][26][27][28] Korábbi kutatások megállapították, hogy a csípőízületi endoprotézis beültetése után fél évvel és egy évvel az ízületi helyzetér-zékelés megegyezik az egészséges személyek ízületi helyzetérzékelésével. [29][30] Ennek oka valószínűsíthetően az, hogy a csípőízületi felszín állapota, az ízületi tok állapota jóval kisebb befolyással van az ízületi helyzetérzé-kelésre, 29 mint az ízületi szalagok és az ízület körüli izmok állapota.…”
Section: Bevezetésunclassified